Knee rotationplasty: motion of the body centre of mass during walking. Issue 4 (December 2016) - Rota, Viviana; Benedetti, Maria Grazia; Okita, Yusuke; Manfrini, Marco; Tesio, Luigi
Abstract : Knee rotationplasty (KRP) is a type of surgery in which the rotated ankle serves as a new knee after being removed for bone tumor. Although this limb salvage surgery is rarely indicated in properly selected patients, it may offer functional advantages over transfemoral amputation, and more durable results compared with a prosthesis. The walking mechanics of adult patients after KRP is believed to be close to that of below-knee amputees. In this study, we evaluated steady-state walking of KRP patients from the viewpoint of the overall muscle power needed to keep the body centre of mass in motion. Three adult patients after KRP, all athletes, were evaluated. Ground reactions during walking were recorded during six subsequent strides on a force treadmill. The positive mechanical work and power sustaining the motion of the centre of mass and the recovery of muscle energy due to the pendulum-like mechanism of walking were computed and compared with those obtained in previous studies from above-knee, below-knee amputees and healthy individuals. In KRP patients, walking was sustained by a muscle power output which was 1.4–3.6 times lower during the step performed on the rotated limb than on the subsequent step. The recovery of muscle energy was slightly lower (0.9) or higher (1.3–1.4 times) on the affected side. In two out of the three KRP patients, our findings were more similar to those from above-knee amputees than to those from below-knee amputees. After KRP, the rotated limb does not necessarily provide the same power provided by below-knee amputation. This may have a relevance for the paralympic classification of KRP athletes.